Distribution of the cyanophyte Trichodesmium (Oscillatoriaceae) in the eastern Caribbean Sea: influence of the Orinoco River - Navarro, Ana (2000)
Orinoco River influence in the Caribbean Sea, characterized by high nutrient input, causes a decrease of Trichodesmium populations. The Caribbean Time Series (CaTS) station, south of Puerto Rico (17°36'N 67°00'W), was monitored for 25 months in order to observe the Trichodesmium abundance pattern and the presence of the river plume. In general, mean Trichodesmium abundance was higher at the surface and decreased with depth; The mean upper Waler column (surface to 20 m) abundance was 54.1t32.6 col/m3. Within the sampling period, abundance was highly variable (1-700 col/m3). Correlation between Trichodesmium abundance and wind speed (p=0.002), chlorophyll a concentration (p=0.001), nitrate (p=0.02) and silicate (p=0. 003)concentrations were statistically significant. However, Trichodesmium abundance was not correlated with salinity (p=0.70), temperature (p=0.16) and seawater density (p=0.71) variatious at CaTS. Eastern Caribbean regions highly influenced by the Orinoco River discharge were devoid of Trichodesmium colonies.